(3aj abg GdChQGb GdfbOjI hGdHfc (B:s (3OQGSI abgjI hbGQfI (B/s - (3GdHQhLQOj, eUWais; (3GdYdhj, YHO GdQMeGf s; (3JYQjHs ((3HjQhJ(B: s (3OGQ GdgGOj(B, s, 2005)
(3jVe GdNWhW GdYQjVI, GdGMcGe GdabgjI ddfbO, GdHfc, GdGMcGe GdabgjI ddeYGedGJ GdeUQajIs
Keywords: (3GdGhQGb GdeGdjIs; (3GdHfhcs; (3GdfbhOs